Academic achievement and employment in young adults with end‐stage kidney disease. Issue 1 (2nd October 2018) - Murray, Peter D.; Brodermann, Maximillian H.; Gralla, Jane; Wiseman, Alexander C.; Harden, Paul N.
SUMMARY: Background: Young adults with end‐stage kidney disease (ESKD) are at a pivotal stage of life: progressing through education, seeking employment and developing relationships. We set out to explore how ESKD impacts education and employment attainment in a matched UK and USA patient cohort. Moreover, we aimed to determine if there were significant differences in reported perceptions of impact. Design: A mixed methods design combining previously validated quantitative questionnaire surveys and qualitative semi‐structured interviews. Participants: Young people with ESKD aged 18–30 years (N = 27), attending single‐centre follow‐up in Oxford, UK were matched with 27 comparable young people aged 19–30 years, under follow‐up in Denver, USA. Twelve of these patients from Denver were selected for interview. Measurements: Self‐report questionnaires surveyed patient demographics, educational and employment achievement and experiences. Questionnaire categorical data for matched pairs were analysed using Bowker's test of symmetry. Sequential flow analyses of interview content delineated perception patterns through thematic coding. Results: Sixty percent of non‐student Oxford participants were employed compared with 41% in Denver (p = 0.023). Forty‐four percent of Oxford patients compared with 52% in Denver, reported illness had made it difficult to gain employment (p = 0.88). In Oxford, 32% completed high school as their highest educational achievement, versus 68% in Denver (p = 0.22). Qualitative themes included fatigue, self‐esteem loss, social isolation and low mood. The impact of dialysis and poor understanding from educators/employers resulted in lost work time, and/or limited educational attainment. Conclusion: ESKD profoundly impacts on education and employment of young adults in the United States and United Kingdom, generating substantial barriers. Poor understanding appears prevalent amongst educators and employers. Healthcare providers must recognise these problems and invest resources towards tailored support in order to improve associated psychosocial and clinical outcomes.